Mental health impact of COVID-19 on Saudi families and children with special educational needs and disabilities in Saudi Arabia: A national perspective - Alenezi, Shuliweeh; Temsah, Mohamad-Hani; Alyahya, Ahmed S.; Almadani, Ahmad H.; Almarshedi, Afnan; Algazlan, Maha S.; Alnemary, Faisal; Bashiri, Fahad A.; Alkhawashki, Samah Hazem; Altuwariqi, Maram Hani; Alsedrani, Rafif; Alkhiri, Aqeel; et al. (Frontiers in Public Health, 2022)
Introduction: The COVID-19 pandemic revealed a multidimensional impact on mental health due to health concerns, social distancing and lockdowns, job loss, and limits in institutional support. Accordingly, COVID-19 may disproportionally impact families with special educational needs and disabilities (SEND) due to the already high prevalence of mental health conditions in children with SEND and their parents. Hence, it is essential to determine the short-term impact of the pandemic on the mental health of families with SEND to identify their ongoing health, including psychological wellbeing and support needs. The current study examines the anxiety level and concerns of children with SEND and their parents living in Saudi Arabia. Methodology: A cross-sectional national study design was utilized as a part of an international consortium using an online Arabic survey. Data collection occurred from May to July 2020 on Ministry of Human Resources and Social Development beneficiaries. The sample consisted of 1848 parents of children with SEND aged between 1 and 18 years (Mean = 9.66; SD = 4.31). A descriptive and bivariant analysis is reported. Results: Parental worries on all those concerns when the pandemic started were significantly higher than before the pandemic, p<0.050. Parental perceived general anxiety had risen significantly across time, p<0.001, and their perceived anxiety when the pandemic started exceeded their anxiety before the pandemic, p<0.001. SEND children's general anxiety had risen significantly across time (from before the pandemic to when it had started then to during the pandemic), p<0.001. The children's general worries at the start of the pandemic had correlated significantly and positively with their anxiety, adaptive, maladaptive, and coping efficacy, and parental anxiety scores, p<0.010 each. Conclusion: Anxiety levels were high in SEND and their caregivers before and during COVID-19. At the start of the pandemic, the anxiety, adaptive, maladaptive, coping efficacy, and parental anxiety scores of the SEND children were significantly and favorably correlated. These findings support the notion of SEND-specific anxiety and patterns of coping in SNED and their caregivers. It also attests to the institutional support required for this specifically vulnerable population during epidemics.